Cerebrovascular reactivity in migraineurs - Sousa, Arthur de Carvalho Jatobá e; Gomes, Ciro Martins; Coelho, Rodolfo de Souza; Teixeira, Ricardo Afonso (Headache Medicine, 2011)
Cerebrovascular reactivity (CR) assessed by transcranial Doppler (TCD) has been evaluated among migraineurs with conflicting results. We assessed the CR using the breath holding index (BHI) among 228 migraineurs during ictal or interictal phase and 56 controls. Migraineurs exhibited increased BHI values in the interictal phase and reduced BHI in the ictal phase when compared to controls.